Laminate

By using specific polyaryl ester in the laminated body of the high-frequency circuit substrate, the problem of difficulty in taking into account low dielectric characteristics, low water absorption and adhesion in the prior art is solved, and multiple excellent properties of the laminated body are achieved.

CN119731024AActive Publication Date: 2025-03-28FUJIFILM CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380059932.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-30
Filing Date
2023-09-15
Publication Date
2025-03-28
Estimated Expiration
2043-09-15

AI Technical Summary

Technical Problem

The prior art is difficult to take into account the low dielectric properties, low water absorption and adhesion between the polymer layer and the copper layer in the high-frequency circuit substrate.

Method used

A laminated structure with a specific polyarylester is adopted, wherein the polyarylester has a repeating unit I and a repeating unit II represented by formula (II), and the repeating unit I is selected from at least one of a group including a repeating unit represented by formula (I-A), a repeating unit represented by formula (I-B), and a repeating unit represented by formula (I-C).

Benefits of technology

The low dielectric characteristics, low water absorption and excellent adhesion between the polymer layer and the copper layer are achieved, which significantly improves the performance of the high-frequency circuit substrate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005272191230000051
    Figure BDA0005272191230000051
  • Figure BDA0005272191230000061
    Figure BDA0005272191230000061
  • Figure BDA0005272191230000062
    Figure BDA0005272191230000062
Patent Text Reader

Abstract

The present invention addresses the problem of providing a laminate that has excellent low dielectric properties, low water absorbency, and adhesion. This laminate has a copper layer and a polymer layer, and is characterized in that the polymer layer contains a polyarylate having at least one repeating unit I selected from the group consisting of repeating units represented by formula (I-A), repeating units represented by formula (I-B), and repeating units represented by formula (I-C), and a repeating unit II represented by formula (II).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a laminated body. Background Art

[0002] The speed and capacity of signals in mobile communication devices such as mobile phones, network infrastructure devices such as servers and routers, and electronic devices such as large computers are increasing year by year, and 5G (fifth generation mobile communication system) in particular is expected to grow rapidly. These electronic devices, for example, are equipped with high-frequency circuit substrates (for example, printed circuit boards such as rigid substrates and flexible substrates, etc.). In addition, in recent years, as an application using such high-frequency signals, the practical application and practical plans of new systems using high-frequency wireless signals in the field of ITS (Intelligent Transport Systems) (for example, related to automobiles and transportation systems, etc.) and indoor short-range communications are also making progress, and high-frequency circuit substrates are also used in these devices.

[0003] In such a high-frequency circuit substrate, a laminate having a polymer layer and a metal layer (for example, metal copper, metal aluminum, etc.) is often used.

[0004] As a polymer constituting the polymer layer, for example, Patent Document 1 discloses “a polyarylate resin comprising a dihydric phenol residue represented by the general formula (1) and aromatic dicarboxylic acid residues represented by the general formulas (2) and (3)”.

[0005] Previous technical literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2018-066018 Summary of the invention

[0008] Technical issues to be solved by the invention

[0009] Laminated bodies used in high-frequency circuit boards and the like are required to have excellent low dielectric properties and low water absorption properties, and also to have excellent adhesion between the polymer layer and the copper layer.

[0010] The present inventors have studied the invention described in Patent Document 1 and have found that it is difficult to achieve low dielectric properties, low water absorption, and adhesion at the same time.

[0011] Therefore, an object of the present invention is to provide a laminate having excellent low dielectric properties, low water absorption, and adhesion.

[0012] Means for solving technical problems

[0013] As a result of intensive studies on the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by the following configuration.

[0014] [1]

[0015] A laminated body comprising a copper layer and a polymer layer, wherein:

[0016] The polymer layer contains polyarylate,

[0017] The polyarylate has a repeating unit I and a repeating unit II represented by formula (II) described later, wherein the repeating unit I is selected from at least one of the group consisting of a repeating unit represented by formula (IA) described later, a repeating unit represented by formula (IB) described later, and a repeating unit represented by formula (IC) described later.

[0018] [2]

[0019] The laminate according to [1], wherein

[0020] The polymer layer further contains a liquid crystal polymer different from the polyarylate.

[0021] 〔3〕

[0022] The laminate according to [1] or [2], wherein

[0023] The above-mentioned polyarylate has a cross-linked structure.

[0024] [4]

[0025] The laminate according to any one of [1] to [3], wherein

[0026] The polyarylate has only a repeating unit represented by the formula (I-Aa) described below as the repeating unit I.

[0027] Effects of the Invention

[0028] According to the present invention, it is possible to provide a laminate having excellent low dielectric properties, low water absorption, and adhesion. DETAILED DESCRIPTION

[0029] In the present specification, a numerical range expressed using "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0030] In the present specification, when a polymer has a plurality of repeating units having the same representation (represented by the same general formula), each repeating unit may be the same or different.

[0031] [Laminated body]

[0032] The laminate of the present invention comprises a copper layer and a polymer layer, wherein the polymer layer contains polyarylate, the polyarylate comprises a repeating unit I and a repeating unit II represented by formula (II), and the repeating unit I is selected from at least one of the group consisting of a repeating unit represented by formula (IA), a repeating unit represented by formula (IB) and a repeating unit represented by formula (IC).

[0033] Hereinafter, a polyarylate having a repeating unit I and a repeating unit II represented by formula (II) is also referred to as a "specific polyarylate", wherein the repeating unit I is selected from at least one of the group consisting of a repeating unit represented by formula (IA), a repeating unit represented by formula (IB) and a repeating unit represented by formula (IC).

[0034] The laminate of the present invention has a polymer layer containing a specific polyarylate.

[0035] As mentioned above, in high-frequency circuit substrate, it is necessary to meet the required standards for various characteristics such as low dielectric properties simultaneously. In the polyarylate of prior art (for example, Comparative Example 1 etc.), it is confirmed that low dielectric properties and low water absorption do not meet the required standards, and the adhesion with the copper layer derived from circuit wiring is also poor. On the other hand, it is known that in the case of using a polymer layer containing a polyarylate with a specific repeating unit such as a specific polyarylate, low dielectric properties, low water absorption and the adhesion of the polymer layer to the copper layer are all excellent, and have a remarkable effect that is difficult to predict.

[0036] Hereinafter, obtaining at least one of the effects of more excellent low dielectric properties, more excellent low water absorption, and more excellent adhesion between the polymer layer and the copper layer is also referred to as “more excellent effects of the present invention”.

[0037] Hereinafter, each member that the laminate may have will be described in detail.

[0038] <Copper layer>

[0039] The laminated body has a copper layer.

[0040] The copper layer is not particularly limited as long as it is a layer composed of metal copper.

[0041] The copper layer (preferably the interface with the polymer layer) may be subjected to a surface modification treatment.

[0042] Examples of the surface modification treatment include discharge treatments such as corona discharge treatment, glow discharge treatment, plasma discharge treatment, and sputtering treatment, ultraviolet treatment, electron beam treatment, and silane coupling treatment.

[0043] Examples of the copper layer include rolled copper foil and electrolytic copper foil.

[0044] Examples of rolled copper foil include TPC foil (manufactured by JX Metal), HA foil (manufactured by JX Metal), HA-V2 foil (manufactured by JX Metal), and C1100R (manufactured by MITSUI SUMITOMO METAL MINING BRASS & COPPER CO., LTD.).

[0045] Examples of the electrolytic copper foil include CF-T4X-SV-18 (manufactured by FUKUDA METAL FOIL & POWDER CO., LTD.), F0-WS-18 (manufactured by Furukawa Electric Co., Ltd.), NC-WS-20 (manufactured by Furukawa Electric Co., Ltd.), YGP-12 (manufactured by NIPPON DEN CORP.), GTS-18 (manufactured by Furukawa Electric Co., Ltd.), and F2-WS-12 (manufactured by Furukawa Electric Co., Ltd.).

[0046] The copper layer may have a wiring pattern.

[0047] As a method of forming a wiring pattern on the copper layer, for example, a well-known etching process can be mentioned.

[0048] The surface roughness Rz of the copper layer (preferably the interface with the polymer layer) is preferably 2.0 μm or less, more preferably 1.0 μm or less, and the lower limit is preferably 0.01 μm or more.

[0049] The surface roughness Rz can be measured by a known method.

[0050] The thickness of the copper layer is preferably 5 to 50 μm, more preferably 9 to 35 μm.

[0051] <Polymer layer>

[0052] The laminate has a polymer layer containing a specific polyarylate.

[0053] The laminate may have a single layer or multiple layers (preferably 2 or 3) of polymer layers. In other words, the polymer layer may be any of a single layer and multiple layers. Furthermore, when the polymer layer is multiple layers, each polymer layer may be in direct contact or may have other layers between the polymer layers.

[0054] Furthermore, when the laminate has a plurality of polymer layers, it is sufficient that at least one of the plurality of polymer layers contains the specific polyarylate, and the laminate may have a polymer layer that does not contain the specific polyarylate.

[0055] (Specific polyarylate)

[0056] The specific polyarylate has a repeating unit I and a repeating unit II represented by formula (II), wherein the repeating unit I is at least one selected from the group consisting of a repeating unit represented by formula (IA), a repeating unit represented by formula (IB), and a repeating unit represented by formula (IC).

[0057] The repeating unit I is preferably at least one selected from the group consisting of a repeating unit represented by formula (IA) and a repeating unit represented by formula (IB), more preferably a repeating unit represented by formula (IA), and further preferably a repeating unit represented by formula (I-Aa).

[0058] Furthermore, the specific polyarylate preferably has only the repeating unit represented by the formula (IA) as the repeating unit I, and more preferably has only the repeating unit represented by the formula (I-Aa) as the repeating unit I.

[0059] -Repeating unit represented by formula (IA)-

[0060] [Chemical formula 1]

[0061]

[0062] In formula (IA), R 1 It represents a branched alkyl group having 4 or more carbon atoms.

[0063] R 2 represents a hydrogen atom, a linear alkyl group, or an aryl group which may have a substituent.

[0064] R 3 represents a hydrogen atom, an alkyl group, or an aryl group which may have a substituent.

[0065] Among them, R 1 With R 2 They do not bond to each other to form a ring structure.

[0066] In formula (IA), R 1 It represents a branched alkyl group having 4 or more carbon atoms.

[0067] R 1 The number of carbon atoms in the moiety is preferably 4-20, more preferably 4-15, further preferably 4-10, and particularly preferably 4-8.

[0068] As R 1, for example, 1-methylpropyl, 2-methylpropyl, 1,2-dimethylpropyl, 2,2-dimethylpropyl, 1-ethylpropyl, 1-methylbutyl, 2-methylbutyl, 3-methylbutyl, 1-ethylbutyl, 2-ethylbutyl, 1,1-dimethylbutyl, 1,2-dimethylbutyl, 1,3-dimethylbutyl, 2,2-dimethylbutyl, 3,3-dimethylbutyl, 4-methylpentyl, 1-ethylpentyl, 2-ethylpentyl, 3-ethylpentyl, 1,3-dimethylpentyl, 1,4-dimethylpentyl, 2,4,4-trimethylpentyl, 1-ethylheptyl, 2-ethylheptyl, 3-methylhexyl and 11-methyldodecyl.

[0069] Among them, as R 1 , preferably 1-methylpropyl, 2-methylpropyl, 1-methylbutyl, 3-methylbutyl, 1-ethylpropyl, 1-ethylbutyl, 1-ethylpentyl, 1-ethylhexyl, 1-ethylheptyl or 2,4,4-trimethylpentyl, more preferably 2-methylpropyl, 1-ethylbutyl, 1-ethylpentyl, 2,4,4-trimethylpentyl or 1-ethylheptyl.

[0070] In formula (IA), R 2 represents a hydrogen atom, a linear alkyl group, or an aryl group which may have a substituent.

[0071] R 2 The number of carbon atoms of the linear alkyl group represented is preferably 1 to 10, more preferably 1 to 6, and even more preferably 1 to 4.

[0072] As R 2 The straight-chain alkyl group represented by is preferably a methyl group or an ethyl group, and more preferably a methyl group.

[0073] Can have R 2 The number of carbon atoms of the aryl group of the substituent represented is preferably 6 to 26, more preferably 6 to 20, further preferably 6 to 15, particularly preferably 6 to 12, and most preferably 6 to 10.

[0074] As can have R 2 The aryl group of the substituent represented by is preferably phenyl, 4-methoxyphenyl, 4-acetoxyphenyl, 1-naphthyl or 2-naphthyl.

[0075] As R 2 , preferably a hydrogen atom or a methyl group.

[0076] In formula (IA), R 3 represents a hydrogen atom, an alkyl group, or an aryl group which may have a substituent.

[0077] R 3 The alkyl group represented may be any of linear, branched, and cyclic.

[0078] R 3 The number of carbon atoms of the alkyl group represented is preferably 1-10, more preferably 1-6, and even more preferably 1-4.

[0079] As R 3 The alkyl group represented is preferably a methyl group or an ethyl group, and more preferably a methyl group.

[0080] Can have R 3 The meaning of the aryl group of the substituent represented by 2 The aryl group of the substituent represented has the same meaning and the preferred embodiment is also the same.

[0081] As R 3 , preferably a hydrogen atom or a methyl group.

[0082] In formula (IA), R 1 With R 2 They do not bond to each other to form a ring structure.

[0083] In R 1 With R 2 When the nanoparticles are not bonded to each other to form a ring structure, various properties such as low dielectric properties are excellent.

[0084] As the repeating unit represented by formula (IA), a repeating unit represented by formula (I-Aa) is preferred.

[0085] [Chemical formula 2]

[0086]

[0087] -Repeating unit represented by formula (IB)-

[0088] [Chemical formula 3]

[0089]

[0090] In formula (IB), R 4 represents a hydrogen atom, a linear alkyl group, or an aryl group which may have a substituent.

[0091] R 5 represents a hydrogen atom, an alkyl group, or an aryl group which may have a substituent.

[0092] n represents an integer of 2 to 20.

[0093] In formula (IB), R 4 represents a hydrogen atom, a linear alkyl group, or an aryl group which may have a substituent.

[0094] R 4 The meaning of the straight chain alkyl represented by R 2The linear alkyl groups represented have the same meanings and preferred aspects are also the same.

[0095] Can have R 4 The meaning of the aryl group of the substituent represented by 2 The aryl group of the substituent represented has the same meaning and the preferred embodiment is also the same.

[0096] As R 4 , preferably a hydrogen atom or a methyl group.

[0097] In the formula (IB), n represents an integer of 2-20.

[0098] When n is an integer of 2 to 20, the solubility of the specific polyarylate in a solvent and the compatibility with the functional material are easily improved, so that the polymer layer is easily formed and its function is easily expressed.

[0099] n is preferably an integer of 3 to 20, more preferably an integer of 4 to 20, further preferably an integer of 4 to 15, particularly preferably an integer of 5 to 13, and most preferably an integer of 6 to 10.

[0100] -Repeating unit represented by formula (IC)-

[0101] [Chemical formula 4]

[0102]

[0103] In formula (IC), R 6 and R 7 represents a hydrogen atom, an alkyl group, or an aryl group which may have a substituent.

[0104] In formula (IC), R 6 and R 7 The meaning of R 3 The meanings are the same and the preferred aspects are also the same.

[0105] Specific examples of the repeating unit represented by formula (IA) are shown below. In the formula, Me represents a methyl group.

[0106] [Chemical formula 5]

[0107]

[0108] Specific examples of the repeating unit represented by formula (IB) are shown below. In the formula, Me represents a methyl group.

[0109] [Chemical formula 6]

[0110]

[0111] [Chemical formula 7]

[0112]

[0113] Specific examples of the repeating unit represented by formula (IC) are shown below.

[0114] [Chemical formula 8]

[0115]

[0116] The content of the repeating unit I in the specific polyarylate is preferably 10% by mass or more, more preferably 20% by mass or more, further preferably 30% by mass or more, and particularly preferably 40% by mass or more, relative to the total mass of the specific polyarylate. The upper limit is preferably 70% by mass or less, more preferably 60% by mass or less, relative to the total mass of the specific polyarylate.

[0117] The content of the repeating unit represented by formula (IA) in the specific polyarylate is preferably 10% by mass or more, more preferably 20% by mass or more, further preferably 30% by mass or more, and particularly preferably 40% by mass or more, relative to the total mass of the specific polyarylate. The upper limit is preferably 70% by mass or less, more preferably 60% by mass or less, relative to the total mass of the specific polyarylate.

[0118] The content of the repeating unit represented by formula (IB) in the specific polyarylate is preferably 10% by mass or more, more preferably 20% by mass or more, further preferably 30% by mass or more, and particularly preferably 40% by mass or more, relative to the total mass of the specific polyarylate. The upper limit is preferably 70% by mass or less, more preferably 60% by mass or less, relative to the total mass of the specific polyarylate.

[0119] The content of the repeating unit represented by formula (IC) in the specific polyarylate is preferably 10% by mass or more, more preferably 20% by mass or more, relative to the total mass of the specific polyarylate. The upper limit is preferably 70% by mass or less, more preferably 60% by mass or less, further preferably 50% by mass or less, and particularly preferably 40% by mass or less, relative to the total mass of the specific polyarylate.

[0120] -Repeat Unit II-

[0121] The specific polyarylate has a repeating unit II represented by the formula (II).

[0122] [Chemical formula 9]

[0123]

[0124] In formula (II), R c represents an alkyl group, an aryl group which may have a substituent, or a halogen atom.

[0125] r represents an integer of 0-4.

[0126] Rc The alkyl group represented by R c The meanings of the aryl groups of the substituents represented by 3 The alkyl group represented by R 3 The aryl group of the substituent represented has the same meaning and the preferred embodiment is also the same.

[0127] As R c Examples of the halogen atom represented by include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.

[0128] As R c , preferably a hydrogen atom or a methyl group.

[0129] r is preferably 0 or 2, more preferably 0.

[0130] The content of the repeating unit II in the specific polyarylate is preferably 10% by mass or more, more preferably 20% by mass or more, further preferably 30% by mass or more, and particularly preferably 40% by mass or more, relative to the total mass of the specific polyarylate. The upper limit is preferably 70% by mass or less, more preferably 60% by mass or less, relative to the total mass of the specific polyarylate.

[0131] The specific polyarylate may have other repeating units in addition to the above-mentioned respective repeating units.

[0132] As another repeating unit, a repeating unit derived from dicarboxylic acid is mentioned, for example.

[0133] Examples of the dicarboxylic acid include 4,4′-diphenyl ether dicarboxylic acid, 1,4-cyclohexane dicarboxylic acid, terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalene dicarboxylic acid, 2,3-naphthalene dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, undecanedioic acid, dodecanedioic acid, tridecanedioic acid, tetradecanedioic acid, pentadecane dioic acid, octadecanedioic acid, nonadecanedioic acid, and eicosanedioic acid.

[0134] As the dicarboxylic acid, 4,4′-diphenyl ether dicarboxylic acid, 2,6-naphthalene dicarboxylic acid or terephthalic acid is preferred.

[0135] The content of other repeating units in the specific polyarylate is preferably 10 to 60% by mass, more preferably 20 to 50% by mass, and further preferably 30 to 50% by mass, based on the total mass of the specific polyarylate.

[0136] The specific polyarylate preferably has a cross-linked structure.

[0137] The crosslinked structure is not particularly limited, but when the polymer layer is formed using a polymer layer-forming composition containing a crosslinking agent described later, a crosslinked structure in which specific polyarylates are linked to each other in a part of the structure is preferred.

[0138] The weight average molecular weight of the specific polyarylate is preferably 50,000 to 250,000, more preferably 80,000 to 180,000, and further preferably 100,000 to 150,000.

[0139] In this specification, unless otherwise specified, the molecular weight of a polymer such as a specific polyarylate is a weight average molecular weight. The weight average molecular weight is a polystyrene conversion value obtained by gel permeation chromatography (GPC). As the eluent in GPC, tetrahydrofuran is preferred. The preferred embodiment of the above-mentioned weight average molecular weight is a polystyrene conversion value measured using tetrahydrofuran as an eluent.

[0140] The specific polyarylate may be used alone or in combination of two or more.

[0141] The content of the specific polyarylate is often 1 to 100% by mass, preferably 5 to 65% by mass, more preferably 15 to 55% by mass, and further preferably 20 to 45% by mass, based on the total mass of the polymer layer.

[0142] In this specification, when the laminate has a single polymer layer, the content of the specific polyarylate is a value relative to the total mass of the single polymer layer. In addition, when the laminate has multiple polymer layers, the content of the specific polyarylate is a value relative to the total mass of each single polymer layer, not a value relative to the total mass of the multiple polymer layers.

[0143] Unless otherwise specified, the contents of the following components are the same as those described above.

[0144] 〔Liquid crystal polymer〕

[0145] The polymer layer may contain a liquid crystal polymer.

[0146] The liquid crystal polymer is a polymer different from the specific polyarylate and is a polymer that does not correspond to the specific polyarylate (does not satisfy the requirements of the specific polyarylate).

[0147] The liquid crystal polymer may be a thermotropic liquid crystal polymer that exhibits liquid crystallinity in a molten state.

[0148] Examples of the thermotropic liquid crystal polymer include thermotropic liquid crystal polyesters and thermotropic liquid crystal polyester amides.

[0149] Also, at least one structure selected from the group consisting of an imide bond, a urethane bond, a carbodiimide bond, a carbonate bond, and an isocyanurate bond may be introduced into the thermotropic liquid crystal polyester and the thermotropic liquid crystal polyester amide.

[0150] The liquid crystal polymer may have a repeating unit derived from p-hydroxybenzoic acid and / or a repeating unit derived from 6-hydroxy-2-naphthoic acid.

[0151] The liquid crystal polymer preferably includes a repeating unit represented by any one of Formula (LC1) to Formula (LC4).

[0152] [Chemical formula 10]

[0153]

[0154] [Chemical formula 11]

[0155]

[0156] In formula (LC2), Ar 1 It represents a phenyl group, a biphenyl group, a naphthyl group, an anthracenyl group or a phenanthryl group which may have a substituent.

[0157] As Ar 1 , preferably a phenyl group which may have a substituent or a biphenyl group which may have a substituent.

[0158] As Ar 1 The substituent that the group represented may have is preferably an alkyl group, an alkoxy group or a fluorine atom.

[0159] [Chemical formula 12]

[0160]

[0161] [Chemical formula 13]

[0162]

[0163] The content of the repeating unit represented by the formula (LC1) is preferably 10 to 80 mol %, more preferably 50 to 65 mol %, based on the total mass of the liquid crystal polymer.

[0164] The content of the repeating unit represented by the formula (LC2) is preferably 1 to 50 mol %, more preferably 15 to 25 mol %, based on the total mass of the liquid crystal polymer.

[0165] The content of the repeating unit represented by the formula (LC3) is preferably 1 to 50 mol %, more preferably 10 to 25 mol %, based on the total mass of the liquid crystal polymer.

[0166] The content of the repeating unit represented by the formula (LC4) is preferably 1 to 50 mol %, more preferably 1 to 10 mol %, based on the total mass of the liquid crystal polymer.

[0167] The liquid crystal polymer may be in the form of particles.

[0168] When the polymer layer contains a liquid crystal polymer, the polymer layer preferably further contains a specific polyarylate.

[0169] The average particle size of the particulate liquid crystal polymer is preferably 1 to 30 μm, more preferably 3 to 25 μm, and further preferably 5 to 20 μm.

[0170] The average particle size can be measured using, for example, a dynamic scattering particle size distribution measuring apparatus.

[0171] The melting point of the liquid crystal polymer is preferably 300° C. or higher, more preferably 305° C. or higher, and further preferably 310° C. or higher. The upper limit is preferably 350° C. or lower, more preferably 345° C. or lower, and further preferably 340° C. or lower.

[0172] The melting point can be measured in accordance with the test methods of ISO 11357 and ASTM D3418 using a differential scanning calorimeter manufactured by Hitachi High-Tech Science Corporation or the like.

[0173] The liquid crystal polymers may be used alone or in combination of two or more.

[0174] The content of the liquid crystal polymer is preferably 20 to 95% by mass, more preferably 30 to 85% by mass, and further preferably 40 to 75% by mass, based on the total mass of the polymer layer.

[0175] (Other polymers)

[0176] The polymer layer may contain other polymers than the specific polyarylate.

[0177] Examples of other polymers include polyarylates other than the specific polyarylates, polymers having repeating units derived from styrene, polytetrafluoroethylene, polyethylene, polypropylene, and cycloolefin polymers.

[0178] The polyarylate other than the above-mentioned specific polyarylate may have a cross-linked structure. As the cross-linked structure, the cross-linked structure that the specific polyarylate may have is preferred.

[0179] The thickness of the polymer layer is preferably 1 to 100 μm, more preferably 2 to 60 μm.

[0180] In this specification, when the laminate has a single polymer layer, the thickness of the polymer layer is the thickness of the single polymer layer. And, when the laminate has multiple polymer layers, the thickness of the polymer layer is the thickness of each single polymer layer, not the total thickness of the multiple polymer layers.

[0181] Furthermore, when the laminate has a plurality of polymer layers, the total thickness of the plurality of polymer layers is preferably 50 to 500 μm, more preferably 50 to 200 μm.

[0182] [Preferred Embodiments of Laminated Body]

[0183] When the laminate has a single polymer layer, the laminate is preferably a laminate having a copper layer and a single polymer layer in this order (hereinafter also referred to as "laminate X"). In other words, the laminate X has a structure having a single polymer layer on a copper layer, and the whole has a double-layer structure. In addition, the single polymer layer in the laminate X contains a specific polyarylate.

[0184] As a preferred embodiment of the laminate X, embodiment X can be mentioned.

[0185] Aspect X: A laminate comprising a copper layer and a single polymer layer, wherein the single polymer layer contains a specific polyarylate.

[0186] Furthermore, the single polymer layer preferably further contains at least one of a liquid crystal polymer and a specific polyarylate having a cross-linked structure, and more preferably contains a liquid crystal polymer and a specific polyarylate having a cross-linked structure.

[0187] In the case where the laminate has a plurality of polymer layers, the laminate is preferably a laminate having a copper layer and a plurality of polymer layers in sequence (hereinafter also referred to as "laminate Y"). In other words, laminate Y has a structure having a plurality of polymer layers on a copper layer, and the whole laminate has a multilayer structure of more than three layers. In addition, among the plurality of polymer layers in laminate Y, at least the polymer layer (first polymer layer) in direct contact with the copper layer contains a specific polyarylate.

[0188] Preferred embodiments of the laminate Y include Embodiments Y1 to Y8.

[0189] Embodiments Y1 to Y5 are embodiments having two polymer layers, and embodiments Y6 to Y8 are embodiments having three polymer layers. Embodiments having four or more polymer layers may include a embodiment in which the polymer layers constituting embodiments Y1 to Y8 are stacked on the stacked body Y of embodiments Y1 to Y8.

[0190] Aspect Y1: A laminate comprising a copper layer, a first polymer layer, and a second polymer layer in this order, wherein the first polymer layer contains a specific polyarylate and the second polymer layer contains a liquid crystal polymer.

[0191] Embodiment Y2: A laminated body comprising a copper layer, a first polymer layer, and a second polymer layer in this order, wherein the first polymer layer contains a specific polyarylate and a first liquid crystal polymer, and the second polymer layer contains a second liquid crystal polymer.

[0192] The first liquid crystal polymer and the second liquid crystal polymer in aspect Y2 may be the same or different.

[0193] Method Y3: A laminate comprising a copper layer, a first polymer layer and a second polymer layer in sequence, wherein the first polymer layer contains a first specific polyarylate having a cross-linked structure and a first liquid crystal polymer, and the second polymer layer contains a second specific polyarylate not having a cross-linked structure and a second liquid crystal polymer.

[0194] The first liquid crystal polymer and the second liquid crystal polymer in aspect Y3 may be the same or different.

[0195] Method Y4: A laminate comprising, in sequence, a copper layer, a first polymer layer and a second polymer layer, wherein the first polymer layer contains a specific polyarylate and a liquid crystal polymer that may have a cross-linked structure, and the second polymer layer contains other polymers different from any one of the above-mentioned specific polyarylate and the above-mentioned liquid crystal polymer (a polymer that does not correspond to any one of the specific polyarylate and the above-mentioned liquid crystal polymer).

[0196] Mode Y5: A laminate comprising a copper layer, a first polymer layer and a second polymer layer in this order, wherein the first polymer layer contains a first specific polyarylate and a first liquid crystal polymer, and the second polymer layer contains a second specific polyarylate which may have a cross-linked structure and a second liquid crystal polymer.

[0197] The first specific polyarylate and the second specific polyarylate in aspect Y5 may be the same or different.

[0198] The first liquid crystal polymer and the second liquid crystal polymer in aspect Y5 may be the same or different.

[0199] Embodiment Y6: A laminate comprising a copper layer, a first polymer layer, a second polymer layer, and a third polymer layer in this order, wherein the first polymer layer contains a first specific polyarylate, the second polymer layer contains a liquid crystal polymer, and the third polymer layer contains a second specific polyarylate.

[0200] The first specific polyarylate and the second specific polyarylate in aspect Y6 may be the same or different.

[0201] Method Y7: A laminate comprising, in sequence, a copper layer, a first polymer layer, a second polymer layer and a third polymer layer, wherein the first polymer layer contains a first specific polyarylate and a first liquid crystal polymer, the second polymer layer contains a second liquid crystal polymer, and the third polymer layer contains a second specific polyarylate and a third liquid crystal polymer.

[0202] The first specific polyarylate and the second specific polyarylate in aspect Y7 may be the same or different.

[0203] The first to third liquid crystal polymers in aspect Y7 may be the same or different.

[0204] Method Y8: A laminate comprising, in sequence, a copper layer, a first polymer layer, a second polymer layer and a third polymer layer, wherein the first polymer layer contains a first specific polyarylate having a cross-linked structure and a first liquid crystal polymer, the second polymer layer contains a second liquid crystal polymer, and the third polymer layer contains a second specific polyarylate having a cross-linked structure and a third liquid crystal polymer.

[0205] The first specific polyarylate and the second specific polyarylate in aspect Y8 may be the same or different.

[0206] The first to third liquid crystal polymers in aspect Y8 may be the same or different.

[0207] [Method for producing specific arylate]

[0208] The method for producing the specific arylate is not particularly limited, and a known production method can be used.

[0209] The method for producing a specific arylate preferably comprises the following step: mixing a mixture of an alkaline aqueous solution containing a dihydric phenol and an organic solvent with solid 4,4'-biphenyl dicarboxylic acid chloride. The method for producing a specific arylate more preferably comprises the following step: adding solid 4,4'-biphenyl dicarboxylic acid chloride during stirring the mixture of an alkaline aqueous solution containing a dihydric phenol and an organic solvent.

[0210] In the present specification, "solid 4,4'-biphenyl dicarboxylic acid chloride" means solid 4,4'-biphenyl dicarboxylic acid chloride itself, and does not refer to a state (solution or slurry) in which it is mixed with an organic solvent.

[0211] <Method A>

[0212] The method for producing the specific arylate may include method A.

[0213] This is an effective method particularly when the dicarboxylic acid halide is insoluble in the organic solvent of the organic phase or has low solubility.

[0214] In method A, an alkaline aqueous solution of a dihydric phenol is prepared as an aqueous phase, and then a polymerization catalyst is added.

[0215] At this time, in the alkaline aqueous solution of dihydric phenol, the dihydric phenol or its phenolate may not be completely dissolved. In addition, as an organic phase, only an organic solvent that is not miscible with water but dissolves the specific polyarylate is mixed into the above alkaline solution and suspended by stirring. Then, a solid dicarboxylic acid halide such as a powder is added thereto to carry out a polymerization reaction.

[0216] Method A has three advantages.

[0217] The first advantage is that, since the dicarboxylic acid halide is not prepared in advance as a solution or a solvent suspension, hydrolysis can be suppressed before mixing with the alkaline aqueous solution of the dihydric phenol.

[0218] The second advantage is that since the solvent suspension is not handled, there is no need for a complicated operation of transferring the solvent suspension for mixing with the alkaline aqueous solution.

[0219] The third advantage is that an organic solvent can be saved. In order to avoid dicarboxylic acid halide being processed as a solvent suspension, it is possible to consider diluting with a large amount of solvents and making a solution. In contrast, in the method A adding a solid dicarboxylic acid halide, since it is not necessary to dissolve the dicarboxylic acid halide itself completely, the usage amount of the organic solvent can be reduced. As a result, it is possible to improve manufacturing efficiency and save an organic solvent.

[0220] Furthermore, the polymerization catalyst may be added in advance to the aqueous phase or to the organic phase.

[0221] Examples of the base used in preparing the aqueous dihydric phenol solution include sodium hydroxide, potassium hydroxide and lithium hydroxide. The base is usually used in an amount of 2 to 5 times the number of moles of the dihydric phenol, that is, 1 to 2.5 equivalents to the hydroxyl group.

[0222] In the method A among the methods for producing a specific polyarylate, it is preferred that a monomer derived from the repeating unit I is used as a dihydric phenol component from the viewpoint of improving the properties of the obtained specific arylate.

[0223] From the viewpoint of workability during production, solid 4,4′-biphenyldicarboxylic acid chloride preferably does not contain an organic solvent.

[0224] When 4,4'-biphenyl dicarboxylic acid chloride may contain an organic solvent, the content of the organic solvent relative to the total amount of solid 4,4'-biphenyl dicarboxylic acid chloride and the organic solvent is preferably 20 mass % or less, more preferably 10 mass % or less, and even more preferably 5 mass % or less.

[0225] In the interfacial polymerization of the method for producing a specific polyarylate, it is preferred to use a compound represented by the following formula (S) together with a dihydric phenol from the viewpoint of improving the properties of the obtained specific polyarylate and further controlling the molecular weight during polymerization.

[0226] HOR a (S)

[0227] In formula (S), R a It represents a monovalent organic group.

[0228] As the monovalent organic group, an alkyl group or an aryl group is preferred.

[0229] R a The alkyl group represented may be either linear or branched.

[0230] The number of carbon atoms of the alkyl group (including the number of carbon atoms of the substituent when having a substituent) is preferably 1-13, more preferably 1-8, further preferably 1-6, and particularly preferably 1-3.

[0231] R a The number of carbon atoms of the aryl group represented by is preferably 6 to 30 (including the number of carbon atoms of the substituent when having a substituent) , More preferably, it is 6 to 25, Further preferably, it is 6 to 20, Especially preferably, it is 6 to 15, Most preferably, it is 6 to 12. a The aryl group represented by is preferably phenyl.

[0232] Examples of the compound represented by the formula (S) include monohydric phenols and monohydric alcohols used in the method C described below.

[0233] In the method for producing the specific polyarylate, the post-treatment in the method for producing the above-mentioned polymer may be performed.

[0234] Examples of a method for producing a specific polyarylate include a method of polycondensing a monomer derived from the repeating unit I, a monomer derived from the repeating unit II, and, if necessary, other monomers by a conventional method.

[0235] Examples of a method for polycondensing the above-mentioned monomers include methods of polycondensing by interfacial polymerization and solution polymerization, and interfacial polymerization is preferred.

[0236] Interfacial polymerization is a polymerization method for obtaining polyester by mixing a dicarboxylic acid halide dissolved in an organic solvent incompatible with water with a dihydric phenol dissolved in an alkaline aqueous solution. Literature related to interfacial polymerization includes, for example, WMARECKSON, J. Poly. Sci., XL399, 1959 and Japanese Patent Publication No. 40-001959.

[0237] The interfacial polymerization method has a faster reaction than the solution polymerization method, and thus can suppress the hydrolysis of the acid halide, and as a result, a high molecular weight specific polyarylate can be obtained.

[0238] Specifically, an alkaline aqueous solution of a dihydric phenol is prepared as an aqueous phase, and then a polymerization catalyst is added. On the other hand, a dicarboxylic acid halide is dissolved in an organic solvent that is incompatible with water but dissolves a specific polyarylate as an organic phase, and the solution is mixed with the alkaline solution as the aqueous phase, and then a polymerization reaction is carried out while stirring for 1 to 8 hours, preferably at a temperature below 50°C. In addition, all dicarboxylic acid halides may not be dissolved in the organic phase.

[0239] <Method B>

[0240] In the method for producing the above-mentioned specific polyarylate, method B can be used.

[0241] As an organic phase, an organic solvent that is not miscible with water but dissolves the specific polyarylate is mixed with a dicarboxylic acid halide and stirred to obtain a suspension. On the other hand, an alkaline aqueous solution of a dihydric phenol is prepared in another container as an aqueous phase, and then a polymerization catalyst is added. The obtained aqueous phase is added to the above-mentioned suspension to perform a polymerization reaction.

[0242] According to the above method B, the reproducibility of the polymerization process can be improved by preparing the dicarboxylic acid halide in advance as an organic solvent suspension. In addition, compared with the reverse step of adding the solvent suspension of the dicarboxylic acid halide to the alkaline aqueous solution of the dihydric phenol, the above method B does not include the solvent suspension transfer step, so the complexity of the operation is reduced, and the possibility of hydrolysis of the dicarboxylic acid halide in the transfer step is also reduced.

[0243] <Method C>

[0244] In the method for producing the above-mentioned specific polyarylate, method C can be used.

[0245] As the method of the above-mentioned common interfacial polymerization method, an alkaline aqueous solution of dihydric phenol is prepared as an aqueous phase, and then a polymerization catalyst is added. On the other hand, a solution or solvent suspension of a dicarboxylic acid halide is prepared as an organic phase, and it is added to the above-mentioned alkaline solution as an aqueous phase to carry out a polymerization reaction.

[0246] In the interfacial polymerization, from the viewpoint of controlling the molecular weight of the specific polyarylate, an end-capping agent may be used during the polymerization. Also, from the viewpoint of controlling the properties of the specific polyarylate, the end of the specific polyarylate is preferably capped with a monophenol, a monoacid chloride, a monoalcohol, a monocarboxylic acid, or the like.

[0247] Examples of the monohydric phenol include phenol, o-cresol, m-cresol, p-cresol, p-tert-butylphenol, o-phenylphenol, m-phenylphenol, p-phenylphenol, o-methoxyphenol, m-methoxyphenol, p-methoxyphenol, 2,3,5-trimethylphenol, 2,3,6-trimethylphenol, 2,3-xylenol, 2,4-xylenol, 2,5-xylenol, 2,6-xylenol, 3,4-xylenol, 3,5-xylenol, 2-phenyl-2-(4-hydroxyphenyl)propane (sometimes referred to as "p-(α-cumyl)phenol"), 2-phenyl-2-(2-hydroxyphenyl)propane, and 2-phenyl-2-(3-hydroxyphenyl)propane.

[0248] Examples of the monoacid chloride include benzoyl chloride, methanesulfonyl chloride, phenyl chloroformate, acetyl chloride and lauroyl chloride.

[0249] Examples of the monohydric alcohol include methanol, ethanol, n-propanol, isopropanol, n-butanol, 2-butanol, pentanol, hexanol, dodecanol, stearyl alcohol, benzyl alcohol, and phenethyl alcohol.

[0250] Examples of the monocarboxylic acid include acetic acid, propionic acid, octanoic acid, cyclohexanecarboxylic acid, benzoic acid, methylbenzoic acid, phenylacetic acid, p-tert-butylbenzoic acid, and p-methoxyphenylacetic acid.

[0251] Among them, it is preferred to cap the terminal with a monohydric phenol or a monohydric acid chloride, and it is more preferred to cap the terminal with p-tert-butylphenol, 2,3,5-trimethylphenol, 2,3,6-trimethylphenol, benzoyl chloride or acetyl chloride.

[0252] Examples of the polymerization catalyst for interfacial polymerization include quaternary ammonium salts such as tributylbenzylammonium halide, tetrabutylammonium halide, trimethylbenzylammonium halide and triethylbenzylammonium halide; and quaternary phosphonium salts such as tributylbenzylammonium halide, tetrabutylphosphonium halide, trimethylbenzylammonium halide and triethylbenzylammonium halide.

[0253] Among them, tributylbenzylammonium halide, tetrabutylammonium halide, tributylbenzylphosphonium halide, or tetrabutylphosphonium halide is preferred from the viewpoint of easily promoting polymerization.

[0254] Examples of the organic solvent of the organic phase in the interfacial polymerization include chlorine-based solvents such as dichloromethane, 1,2-dichloroethane, chloroform, carbon tetrachloride, chlorobenzene, 1,1,2,2-tetrachloroethane, 1,1,1-trichloroethane, o-dichlorobenzene, m-dichlorobenzene, and p-dichlorobenzene; aromatic hydrocarbons such as toluene, benzene, xylene, and anisole; and tetrahydrofuran.

[0255] Among them, dichloromethane or o-dichlorobenzene is preferred.

[0256] In the case where the dicarboxylic acid halide is insoluble in the organic solvent of the organic phase or has low solubility, other organic solvents can also be used. The organic solvent of the organic phase is preferably an organic solvent that is insoluble in water. In addition, in order to improve the solubility of the dicarboxylic acid halide in the organic phase or to improve the efficiency of the polymerization reaction, and to suppress the hydrolysis of the dicarboxylic acid halide, with the purpose of obtaining a specific arylate of a desired molecular weight, a part or all of the organic phase can also be replaced with an organic solvent that is also soluble in water.

[0257] Examples of effective organic solvents for improving the solubility of the dicarboxylic acid halide in the organic phase include tetrahydrofuran, N,N-dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), dimethyl sulfoxide (DMSO), 1,4-dioxane, and 1,3-dioxolane.

[0258] From the viewpoint of productivity, the concentration of the polymer in the organic phase relative to the organic solvent is preferably high. The content of the specific arylate in the organic phase is preferably 2% by mass or more, more preferably 6% by mass or more, and further preferably 10% by mass or more relative to the total mass of the organic phase. The upper limit is preferably 50% by mass or less relative to the total mass of the organic phase.

[0259] Furthermore, the content of the specific arylate in the aqueous phase and the organic phase is preferably 1% by mass or more, more preferably 3% by mass or more, and further preferably 5% by mass or more, relative to the total mass of the aqueous phase and the organic phase. The upper limit is preferably 50% by mass or less, relative to the total mass of the aqueous phase and the organic phase.

[0260] After the polymerization, acetic acid is added to the obtained specific arylate solution. After the polymerization is completed, the specific arylate solution is repeatedly stirred and washed with water to remove ionic components such as sodium ions, potassium ions, lithium ions, chloride ions and polymerization catalysts contained in the specific arylate solution. The water used for washing can be acidic or alkaline, and washing is repeated until the washing wastewater becomes neutral.

[0261] The specific arylate solution obtained is added dropwise to a poor solvent to precipitate the specific arylate as a solid component. The solid content concentration of the specific arylate solution is preferably 7% by mass or less. In addition, the volume of the poor solvent is preferably 3 times or more of the volume of the polymer solution. Examples of the poor solvent include methanol, ethanol, isopropanol, acetone, acetonitrile and hexane.

[0262] By adding the specific arylate solution to the poor solvent, the residual monomers, alkali and impurities derived from the polymerization catalyst contained in the specific arylate can be reduced. In order to reduce the content of residual monomers and impurities, it is particularly preferred that the immersion time in the poor solvent after the poor solvent is subjected to precipitation treatment is set to more than 1 minute. In addition, as the polymerization catalyst, when trimethylbenzyl ammonium halide and triethylbenzyl ammonium halide with low polymerization activity are used, the immersion time is preferably set to more than 3 minutes. In order to reduce residual monomers and impurities, the above operation can be repeated, that is, the obtained specific arylate is dissolved in a solvent again, and added to the poor solvent for precipitation.

[0263] When manufacturing a specific aryl compound, impurities insoluble in tetrahydrofuran or dichloromethane are sometimes generated. One of the reasons for this is believed to be that 4,4'-biphenyl dicarboxylic acid chloride or the like is used in the introduction of the repeating unit represented by the above formula (II). That is, it is believed that the reason is that when the impurities that may be contained in 4,4'-biphenyl dicarboxylic acid chloride, namely 4,4'-biphenyl dicarboxylic acid or 4-(4-carboxyphenyl)-benzoyl chloride, are brought into the manufacturing process of the above specific aryl compound, an acid anhydride compound is formed as an insoluble impurity as shown in the following scheme.

[0264] This is also considered to be caused by the fact that 4,4′-biphenyldicarboxylic acid or 4-(4-carboxyphenyl)-benzoyl chloride is generated in the polymerization reaction in the production process and then forms an acid anhydride compound as shown in the following scheme.

[0265] [Chemical formula 14]

[0266]

[0267] The polymer layer preferably does not contain such insoluble impurities. As a method for obtaining a specific arylate product containing no insoluble impurities, for example, there is a method of removing the insoluble impurities by treating a solution containing both a polymer and insoluble impurities with various adsorbents.

[0268] Furthermore, for the purpose of suppressing the generation of insoluble impurities themselves, it is preferred to use 4,4'-biphenyl dicarboxylic acid or 4-(4-carboxyphenyl)-benzoyl chloride as an impurity. In 4,4'-biphenyl dicarboxylic acid, the content of 4,4'-biphenyl dicarboxylic acid or the content of 4-(4-carboxyphenyl)-benzoyl chloride is preferably 5% by mass or less, more preferably 1% by mass or less, further preferably 0.5% by mass or less, and particularly preferably 0% by mass.

[0269] [Method for producing laminated body]

[0270] As a method for producing the laminate, for example, a known production method can be mentioned.

[0271] The method for producing a laminated body may be a method for producing a laminated body including the step of applying a polymer layer-forming composition on a copper layer to form a polymer layer.

[0272] When the laminate has a single polymer layer, the method for producing the laminate preferably includes a step of applying a first polymer layer-forming composition on the copper layer to form the first polymer layer.

[0273] In the case where the laminate has a plurality of polymer layers, the method for producing the laminate preferably includes the steps of coating a first polymer layer-forming composition on a copper layer to form a first polymer layer and coating a second polymer layer-forming composition on the obtained first polymer layer to form a second polymer layer. Furthermore, the method for producing the laminate also preferably includes the step of simultaneously coating a plurality of first polymer layer-forming compositions and a first polymer layer-forming composition on a copper layer to form a first polymer layer and a second polymer layer.

[0274] When the laminate has more than three polymer layers, the number of coatings can be appropriately adjusted according to the number of target polymer layers. In addition, when forming multiple polymer layers, the multiple layers can be coated sequentially or simultaneously.

[0275] Furthermore, after coating, a drying treatment or the like may be performed as necessary.

[0276] The method for producing the laminate preferably includes a step of melting a polymer (for example, a specific arylate compound and a liquid crystal polymer) to form a polymer layer and a step of laminating the obtained polymer layer to a copper layer.

[0277] Furthermore, a polymer layer-forming composition may be further coated on the polymer layer formed above to form a single or multiple polymer layer, and a polymer layer-forming composition may be further coated on the copper layer to form a single or multiple polymer layer. When these polymer layers are formed on the formed polymer layer or on the copper layer, they may be formed before or after lamination.

[0278] The step of forming the polymer layer preferably includes a step of kneading a polymer (for example, a specific arylate polymer and a liquid crystal polymer) to obtain particles and a step of forming a film using the obtained particles.

[0279] As a step of forming a polymer layer, for example, International Publication No. 2022 / 138618 can be cited.

[0280] <Polymer layer forming composition>

[0281] The polymer layer-forming composition is a composition for forming a polymer layer.

[0282] The polymer layer-forming composition preferably contains various components that can contain a polymer layer (for example, specific polyarylate, etc.) and a solvent.

[0283] Furthermore, the polymer layer-forming composition preferably contains a crosslinking agent and a curing agent.

[0284] When the polymer layer-forming composition contains a crosslinking agent and a curing agent, the polymer (for example, a specific arylate compound, etc.) in the formed polymer layer has a crosslinked structure.

[0285] Examples of the solvent include chlorine-based solvents such as dichloromethane, 1,2-dichloroethane, chloroform, carbon tetrachloride, chlorobenzene, 1,1,2,2-tetrachloroethane, 1,1,1-trichloroethane, o-dichlorobenzene, and m-dichlorobenzene; aromatic hydrocarbons such as toluene, benzene, and xylene; N-methyl-2-pyrrolidone (NMP), N,N-dimethylacetamide (DMAc), 1,4-dioxane, and tetrahydrofuran.

[0286] The solvent may be used alone or in combination of two or more.

[0287] Examples of the crosslinking agent include aliphatic polyfunctional epoxy compounds such as 1,5-hexadiene diepoxide and 1,4-butanediol diglycidyl ether; aromatic polyfunctional epoxy compounds such as 2,2-bis(4-glycidyloxyphenyl)propane and N,N-diglycidyl-4-glycidyloxyaniline; and heterocyclic-containing polyfunctional epoxy compounds such as triglycidyl isocyanurate.

[0288] The cross-linking agent may be used alone or in combination of two or more.

[0289] The content of the crosslinking agent is preferably 0.1 to 10% by mass, more preferably 1 to 5% by mass, based on the total solid content of the polymer layer-forming composition.

[0290] Examples of the curing agent include imidazoles such as 2-methylimidazole, 2-ethyl-4-methylimidazole, and 2-phenylimidazole; tertiary amines such as 4-dimethylaminopyridine, benzyldimethylamine, 2-(dimethylaminomethyl)phenol, and 2,4,6-tris(dimethylaminomethyl)phenol; and organic phosphines such as triphenylphosphine and tributylphosphine.

[0291] The curing agent may be used alone or in combination of two or more.

[0292] The content of the curing agent is preferably 0.01 to 10% by mass, more preferably 0.1 to 5% by mass, based on the total solid content of the polymer layer-forming composition.

[0293] [use]

[0294] The laminate can be preferably used for a high-frequency circuit substrate, and is preferably used as a laminate for a high-frequency circuit substrate.

[0295] The high-frequency circuit substrate is a circuit substrate that can also work in a high-frequency band (especially 5G). As the above-mentioned high-frequency band, the frequency band above 1 GHz is preferred, the frequency band above 3 GHz is more preferred, and the frequency band above 5 GHz is further preferred. The upper limit is preferably a frequency band below 100 GHz.

[0296] Since the laminate is excellent in low dielectric properties, low water absorption, and adhesion, a high-frequency circuit substrate having small transmission loss even in a high-frequency band, low water absorption, and excellent adhesion can be obtained.

[0297] Example

[0298] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited thereto. In the structural formula shown below, Me represents a methyl group.

[0299] [Various ingredients]

[0300] <Polymer>

[0301] (Specific polyarylate P-01)

[0302] Specific polyarylate P-01 was prepared according to the following protocol.

[0303] [Chemical formula 15]

[0304]

[0305] In a reaction container equipped with a stirring device, 2,2-bis(4-hydroxyphenyl)-4-methylpentane (manufactured by Honshu Chemical Industry Co., Ltd., 11.4493 g), 2,3,5-trimethylphenol (manufactured by Tokyo Chemical Industry Co., Ltd., 0.1750 g), sodium dithionite (manufactured by FUJIFILM Wako Pure Chemical Corporation, 0.0572 g) and water (230 mL) were added to prepare a suspension. Sodium hydroxide (manufactured by FUJIFILM Wako Pure Chemical Corporation, 4.8378 g), benzyltributylammonium chloride (manufactured by FUJIFILM Wako Pure Chemical Corporation, 0.1981 g) and water (150 mL) were added while stirring the suspension at room temperature (20° C.), and stirred for 30 minutes under a nitrogen atmosphere to prepare a solution (slightly turbid) in which the solid substance was substantially dissolved. To the aqueous solution was added o-dichlorobenzene (manufactured by FUJIFILM Wako Pure Chemical Corporation, 210 mL), and after stirring for 30 minutes under a nitrogen atmosphere, powdered 4,4'-biphenyl dicarboxylic acid chloride (manufactured by Tokyo Chemical Industry Co., Ltd., 12.0000 g) was added. After the addition was completed, the reaction was carried out by stirring for 4 hours at room temperature (20°C) under a nitrogen atmosphere. The polymerized solution was diluted with o-dichlorobenzene (300 mL), and the aqueous phase was removed. After washing with a dilute acetic acid solution and ion exchange water, it was put into methanol (manufactured by FUJIFILM Wako Pure Chemical Corporation) to precipitate a polymer. The precipitated polymer was filtered and dried at 50°C. The polymer was dissolved again in 900 mL of tetrahydrofuran (manufactured by FUJIFILM Wako Pure Chemical Corporation) and put into methanol to precipitate a polymer. The precipitated polymer was filtered, washed with methanol, and then dried at 50° C. to obtain a white specific polyarylate P-1 (17.8 g). The weight average molecular weight (Mw) of the specific polyarylate P-1 determined as a molecular weight in terms of polystyrene by gel permeation chromatography (GPC, using tetrahydrofuran as an eluent) was 120,000.

[0306] In the above, powdered 4,4'-biphenyl dicarboxylic acid chloride was added, which corresponds to method A.

[0307] (Specific polyarylate P-02)

[0308] Specific polyarylate P-02 was prepared according to the following protocol.

[0309] [Chemical formula 16]

[0310]

[0311] In a reaction container equipped with a stirring device, 4,4'-(2-ethylhexylene)diphenol (manufactured by Honshu Chemical Industry Co., Ltd., 11.3740 g), 4,4'-decylenebisphenol (manufactured by Honshu Chemical Industry Co., Ltd., 1.3826 g), 2,3,5-trimethylphenol (manufactured by Tokyo Chemical Industry Co., Ltd., 0.1757 g), sodium dithionite (manufactured by FUJIFILM Wako Pure Chemical Corporation, 0.0515 g) and water (240 mL) were added to prepare a suspension. At room temperature (20°C), the suspension was stirred while adding sodium hydroxide (manufactured by FUJIFILM Wako Pure Chemical Corporation, 4.8323 g), benzyltributylammonium chloride (manufactured by FUJIFILM Wako Pure Chemical Corporation, 0.1783 g) and water (160 mL), and stirred for 30 minutes under a nitrogen atmosphere to prepare a solution in which the solid component was roughly dissolved (with some turbidity). To the aqueous solution was added o-dichlorobenzene (manufactured by FUJIFILM Wako Pure Chemical Corporation, 220 mL), and after stirring for 30 minutes under a nitrogen atmosphere, powdered 4,4'-biphenyl dicarboxylic acid chloride (manufactured by Tokyo Chemical Industry Co., Ltd., 12.0000 g) was added. After the addition was completed, the reaction was stirred for 4 hours at room temperature (20°C) under a nitrogen atmosphere. The solution after polymerization was diluted with o-dichlorobenzene (300 mL), and the aqueous phase was removed. After washing with a dilute acetic acid solution and ion exchange water, it was put into methanol (manufactured by FUJIFILM Wako Pure Chemical Corporation) to precipitate a polymer. The precipitated polymer was filtered and dried at 50°C. The polymer was dissolved again in 900mL of tetrahydrofuran (manufactured by FUJIFILM Wako Pure Chemical Corporation) and put into methanol to precipitate a polymer. The precipitated polymer was filtered and washed with methanol, and then dried at 50°C to obtain a white specific polyarylate P-02 (17.5g). The weight average molecular weight (Mw) of the specific polyarylate P-02 determined as a molecular weight converted to polystyrene by gel permeation chromatography (GPC, using tetrahydrofuran as an eluent) was 130,000.

[0312] In the above, powdered 4,4'-biphenyl dicarboxylic acid chloride was added, which corresponds to method A.

[0313] (Specific polyarylate P-03)

[0314] Specific polyarylate P-03 was prepared according to the following protocol.

[0315] [Chemical formula 17]

[0316]

[0317] In a reaction container equipped with a stirring device, 2,2-bis(4-hydroxyphenyl)-4-methylpentane (manufactured by Honshu Chemical Industry Co., Ltd., 6.8697 g), 9,9-bis(4-hydroxy-3-methylphenyl)fluorene (manufactured by Tokyo Chemical Industry Co., Ltd., 6.4109 g), 2,3,5-trimethylphenol (manufactured by Tokyo Chemical Industry Co., Ltd., 0.1757 g), sodium dithionite (manufactured by FUJIFILM Wako Pure Chemical Corporation, 0.0343 g) and water (244 mL) were added to prepare a suspension. At room temperature (20°C), the suspension was stirred while adding sodium hydroxide (manufactured by FUJIFILM Wako Pure Chemical Corporation, 4.8323 g), benzyltributylammonium chloride (manufactured by FUJIFILM Wako Pure Chemical Corporation, 0.1981 g) and water (163 mL), and stirred for 30 minutes under a nitrogen atmosphere to prepare a solution in which the solid substance was roughly dissolved (with some turbidity). Dichloromethane (manufactured by FUJIFILM Wako Pure Chemical Corporation, 250 mL) was added to the aqueous solution, and after stirring for 30 minutes under a nitrogen atmosphere, powdered 4,4'-biphenyl dicarboxylic acid chloride (manufactured by Tokyo Chemical Industry Co., Ltd., 12.0000 g) was added. After the addition was completed, the reaction was stirred for 4 hours at room temperature (20°C) under a nitrogen atmosphere. The solution after polymerization was diluted with dichloromethane (300 mL), and the aqueous phase was removed. After washing with a dilute acetic acid solution and ion exchange water, it was put into methanol (manufactured by FUJIFILM Wako Pure Chemical Corporation) to precipitate a polymer. The precipitated polymer was filtered and dried at 50°C. The polymer was dissolved again in 900mL of tetrahydrofuran (manufactured by FUJIFILM Wako Pure Chemical Corporation) and put into methanol to precipitate a polymer. The precipitated polymer was filtered and washed with methanol, and then dried at 50°C to obtain a white specific polyarylate P-03 (20.1g). The weight average molecular weight (Mw) of the specific polyarylate P-03 determined as a molecular weight converted to polystyrene by gel permeation chromatography (GPC, using tetrahydrofuran as an eluent) was 90,000.

[0318] In the above, powdered 4,4'-biphenyl dicarboxylic acid chloride was added, which corresponds to method A.

[0319] (Polyarylate CP-01)

[0320] With reference to Japanese Patent Application Publication No. 2018-066018, polyarylate CP-01 was obtained.

[0321] [Chemical formula 18]

[0322]

[0323] <Other ingredients>

[0324] ·SEBS: Styrene polymer, Tuftec M1913, manufactured by Asahi Kasei Chemicals Corporation

[0325] LCP: Liquid crystal polymer particles, melting point 320° C., synthesized based on Example 1 of JP-A-2019-116586.

[0326] ·JER630: aminophenol type epoxy resin (JER (registered trademark) 630), manufactured by Mitsubishi Chemical Corporation

[0327] ·2E4MI: 2-ethyl-4-methylimidazole, IsoQure (registered trademark) IM 2E4MI, manufactured by Tokyo Chemical Industry Co., Ltd.

[0328] DCM: dichloromethane

[0329] [Preparation of polymer layer-forming composition]

[0330] As shown in the following table, predetermined amounts of various components were mixed to obtain respective polymer layer-forming compositions.

[0331] [Table 1]

[0332]

[0333] [Preparation of Liquid Crystal Polymer Layer 1]

[0334] The above LCP (liquid crystal polymer particles, 84.9 parts by mass), NOVATEC LD (low-density polyethylene, 12.0 parts by mass) manufactured by Japan Polyethylene Corporation, BOND FAST (registered trademark) E (copolymer of ethylene and glycidyl methacrylate (E-GMA copolymer), 3.0 parts by mass) manufactured by SUMITOMO CHEMICAL COMPANY, LIMITED, and Irganox 1010 (hindered phenolic heat stabilizer, 0.1 parts by mass) manufactured by BASF were mixed and kneaded into pellets using an extruder. The kneaded pelletized polymer was dried at 80° C. for 12 hours using a dehumidified hot air dryer with a dew point temperature of −45° C. to reduce the moisture content to 50 mass ppm or less.

[0335] The obtained pellets were fed into the cylinder from the same feed port of a twin-screw extruder with a screw diameter of 50 mm, heated and kneaded at 270-350°C, and a molten film-like liquid crystal polymer was extruded from a die with a die width of 750 mm and a slit spacing of 300 μm. The uneven thickness of the extruded film-like liquid crystal polymer in the width direction was improved by slightly adjusting the gap of the die lip. In this way, a liquid crystal polymer layer 1 (film-like) with a thickness of 50 μm was obtained.

[0336] [Preparation of Laminated Body A (Examples 1 to 3, 8, 9 and Comparative Example 1)]

[0337] Using an applicator, the polymer layer-forming composition for forming the first layer shown in Table 2 was applied to one surface of the obtained liquid crystal polymer layer 1 while adjusting the flow rate so as to obtain the film thickness after drying shown in Table 2. The applied film was dried at 80° C. for 2 hours to obtain a laminate having a polymer layer A1 corresponding to the first layer shown in Table 2 on the liquid crystal polymer layer 1.

[0338] The surface of the polymer layer A1 in the obtained laminate on the side opposite to the liquid crystal polymer layer 1 is bonded to the bonding surface of a copper foil (manufactured by FUKUDA METAL FOIL & POWDER CO., LTD., CF-T4X-SV-18, thickness 18 μm, surface roughness Rz0.85 μm of the bonding surface (treated surface)), and then pressed at 200°C and 4 MPa for 1 hour using a hot press (manufactured by Toyo Seiki Seisaku-sho, Ltd.), thereby obtaining a laminate having a copper foil, a polymer layer A1 (first layer) and a liquid crystal polymer layer 1 (second layer) in sequence.

[0339] In addition, a polymer layer-forming composition for forming the third layer shown in Table 2 was applied to the surface of the liquid crystal polymer layer 1 of the obtained laminate on the side opposite to the polymer layer A1 using an applicator. The coated film was dried at 80° C. for 2 hours to prepare a laminate A having a polymer layer A2 corresponding to the third layer shown in Table 2 on the liquid crystal polymer layer 1.

[0340] The laminate A includes a copper foil, a polymer layer A1 (first layer), a liquid crystal polymer layer 1 (second layer), and a polymer layer A2 (third layer) in this order.

[0341] [Preparation of Laminated Body B (Examples 4 and 5)]

[0342] The polymer layer-forming composition forming the first layer shown in Table 2 was coated on the treated surface of a copper foil (manufactured by FUKUDA METAL FOIL & POWDER CO., LTD., CF-T4X-SV-18, thickness 18 μm, surface roughness Rz 0.85 μm on the treated surface) while adjusting the flow rate so as to obtain the film thickness after drying shown in Table 2. The coated film was dried at 80° C. for 2 hours to obtain a laminate B having a polymer layer B corresponding to the first layer shown in Table 2 on the copper foil.

[0343] In addition, the laminated body B has a copper foil and a polymer layer B (first layer) in this order.

[0344] [Preparation of Laminated Body C (Examples 6 and 7)]

[0345] The composition for forming the first layer shown in Table 2 was coated on the treated surface of a copper foil (CF-T4X-SV-18, thickness 18 μm, surface roughness Rz 0.85 μm on the treated surface, manufactured by FUKUDA METAL FOIL & POWDER CO., LTD.) while adjusting the flow rate so as to obtain the film thickness after drying shown in Table 2. The coated film was dried at 80° C. for 2 hours to obtain a laminate having a polymer layer C1 corresponding to the first layer shown in Table 2 on the copper foil.

[0346] In addition, a polymer layer-forming composition for forming the second layer shown in Table 2 was applied to the surface of the polymer layer C1 of the obtained laminate on the side opposite to the copper foil using an applicator. The coated film was dried at 80° C. for 2 hours to prepare a laminate C having a polymer layer C2 corresponding to the second layer shown in Table 2 on the polymer layer C1.

[0347] Moreover, the laminated body C has a copper foil, a polymer layer C1 (first layer), and a polymer layer C2 (second layer) in this order.

[0348] [evaluate]

[0349] After removing the copper foil in the laminated bodies of Examples and Comparative Examples by etching (immersion in a 40 mass % iron (III) chloride aqueous solution (manufactured by Wako Pure Chemical, Ltd.) for 6 hours), samples for measuring dielectric properties and water absorption were obtained.

[0350] <Dielectric properties>

[0351] The dielectric properties were evaluated by measuring the dielectric loss tangent at a frequency of 10 GHz using a resonance perturbation method.

[0352] A 10 GHz cavity resonator (CP531 manufactured by Kanto Electronics Application & Development Inc.) was connected to a network analyzer (manufactured by Agilent Technology, "E8363B"), and a measurement sample was inserted into the cavity resonator. In an environment of temperature 25°C and humidity 60% RH, the dielectric loss tangent of the laminate was measured based on the change in the resonant frequency after 96 hours compared with the resonant frequency before insertion, and was evaluated according to the following evaluation criteria.

[0353] 4: Dielectric loss tangent is less than 0.002

[0354] 3: Dielectric loss tangent is greater than 0.002 and less than 0.004

[0355] 2: Dielectric loss tangent is greater than 0.004 and less than 0.006

[0356] 1: Dielectric loss tangent greater than 0.006

[0357] <Water absorption>

[0358] The sample for measurement (about 0.2 g) was cut out and immersed in ion exchange water. After immersion at 25°C for 1 week, water droplets on the surface were wiped off, and the water absorption rate was measured by Karl Fischer vaporization method (measuring device: AQ-2250 vaporization device AQS-225320, reagent used: Aqua Light RS-A (general purpose), measuring temperature 180°C, nitrogen flow rate: 200 mL / min), and evaluated according to the following evaluation criteria.

[0359] 4: Water absorption is less than 0.04% by mass

[0360] 3: Water absorption is 0.04 mass% or more and 0.1 mass% or less

[0361] 2: Water absorption greater than 0.1% by mass and less than 0.2% by mass

[0362] 1: Water absorption greater than 0.2% by mass

[0363] <Adhesion to copper layer>

[0364] Each laminate of the embodiment and the comparative example was cut into a strip of 1 cm × 5 cm to prepare a sample for evaluating adhesion. The adhesion of the obtained sample for evaluation was measured according to the peel strength measurement method described in JIS C 6481 (unit: kN / m). The peeling condition was to peel the copper foil from the sample for evaluation at an angle of 90° relative to the sample for evaluation and at a peeling speed of 50 mm / second. The measurement was performed at 5 locations to obtain the arithmetic mean value, and the evaluation was performed according to the following evaluation criteria.

[0365] 4: Peel strength greater than 15kN / m

[0366] 3: Peel strength is 10 kN / m or more and 15 kN / m or less

[0367] 2: Peel strength is 7kN / m or more and less than 10kN / m

[0368] 1: Peel strength is less than 7kN / m

[0369] Table 2 shows the evaluation results.

[0370] The column of "Type" indicates whether the laminated body A, the laminated body B, or the laminated body C corresponds to the laminated body.

[0371] The columns of "1st layer", "2nd layer" and "3rd layer" of "polymer layer" indicate the structure of each laminate. That is, each laminate has a copper layer, a 1st polymer layer, an optional 2nd polymer layer and a 3rd polymer layer in this order. Specifically, the laminate of Example 1 has a copper layer, a 1st polymer layer (a layer derived from the polymer layer forming composition 1), a 2nd polymer layer (liquid crystal polymer layer 1) and a 3rd polymer layer (a layer derived from the polymer layer forming composition 1) in this order.

[0372] [Table 2]

[0373]

[0374] From the results shown in the table, it was confirmed that the laminate of the present invention was excellent in low dielectric properties, low water absorption, and adhesion.

[0375] When the specific polyarylate includes only the repeating unit represented by the formula (I-Aa) as the repeating unit I, it was confirmed that the effect of the present invention is more excellent (Examples 2, 8, and 9).

Claims

1. A laminate comprising a copper layer and a polymer layer, wherein: The polymer layer contains polyarylate, The polyarylate comprises a repeating unit I and a repeating unit II represented by formula (II), wherein the repeating unit I is at least one selected from the group consisting of a repeating unit represented by formula (IA), a repeating unit represented by formula (IB), and a repeating unit represented by formula (IC), [Chemical formula 1] In formula (IA), R 1 represents a branched alkyl group having 4 or more carbon atoms, R 2 represents a hydrogen atom, a linear alkyl group, or an aryl group which may have a substituent, R 3 represents a hydrogen atom, an alkyl group, or an aryl group which may have a substituent, Among them, R 1 With R 2 They do not bond to each other to form a ring structure. [Chemical formula 2] In formula (IB), R 4 represents a hydrogen atom, a linear alkyl group, or an aryl group which may have a substituent, R 5 represents a hydrogen atom, an alkyl group, or an aryl group which may have a substituent, n represents an integer from 2 to 20, [Chemical formula 3] In formula (IC), R 6 and R 7 represents a hydrogen atom, an alkyl group, or an aryl group which may have a substituent, [Chemical formula 4] In formula (II), R c represents an alkyl group, an aryl group which may have a substituent, or a halogen atom, and r represents an integer of 0-4.

2. The laminate according to claim 1, wherein The polymer layer also contains a liquid crystal polymer different from the polyarylate.

3. The laminate according to claim 1 or 2, wherein: The polyarylate has a cross-linked structure.

4. The laminate according to claim 1 or 2, wherein: The polyarylate has only the repeating unit represented by formula (I-Aa) as the repeating unit I, [Chemical formula 5]

Citation Information

Patent Citations

  • Polyarylate resin, film comprising the same, and laminate

    JP2018066018A

  • Resin film and metal foil laminate

    JP2019116586A

  • Polyarylate resin, film formed from same and laminate

    CN109415499A

  • Insulating film and manufacturing method for insulating film material thereof

    JP2004002735A

  • Optical film and manufacturing method thereof

    JP2009128794A